Antifungal activity of biosynthesized silver nanoparticles mediated by neem leaf extract against aspergillus sp. - Wan Nur Atiqah, Wan Shamsudin; Che Ku Mohammad Faizal, Che Ku Yahya; Siti Hajar Noor, Shaarani (AMG Transcend Association, 2023)
Silver nanoparticles (AgNPs) have attracted considerable attraction as excellent antifungal agents against various pathogens. In the present study, AgNPs were biosynthesized using neem leaf aqueous extract, and their antifungal properties were evaluated against Aspergillus sp. The formation of newly synthesized AgNPs was confirmed through visual observation by a change in the color of the solution, followed by an analysis of their surface plasmon resonance via UV-vis spectrophotometer. Further characterization of its crystalline nature and morphology structure was assessed by X-Ray Diffraction (XRD) and Field-emission Scanning Electron Microscope (FESEM), respectively. The result revealed that the synthesized AgNPs showed UV-vis spectra peak around 421 nm, are crystalline in nature, and have a spherical morphology with an average size of 20.13 ± 3.3 nm in diameter. Furthermore, these AgNPs exhibit excellent antifungal activity against the waterborne pathogen Aspergillus sp. on agar well diffusion assay with a maximum 26.54 ± 1.23 mm zone of inhibition. FESEM image revealed hyphal damage and deformation of fungus when treated with AgNPs, causing retardation of fungus growth for further reproduction. The results suggested that this biosynthesis AgNPs from neem leaf extract has great potential as an alternative antifungal agent for use in water treatment.